MONITORING OF FISH IN THE COASTAL BIOTOPES OF THE SOUTHERN PART OF FAR EASTERN MARINE RESERVE (PETER THE GREAT BAY, JAPAN SEA) - A. I. Markevich (Известия ТИНРО, 2018)
Fish counts by SCUBA visual methods are conducted in the coastal biotopes at Furugelm and Popov Islands and in the Sivuchia, Kalevala, and Pemzovaya Bays in the western Peter the Great Bay in July-August of 2012 and 2014. In total, 23 fish species were registered on transects at Furugelm Island and 11 species at Popov Island in 2012, and in 2014 — 17 fish species at Furugelm Island, 16 at Popov Island, 9 in the Sivuchia Bay, 6 in the Kalevala Bay, and 11 in the Pemzovaya Bay. Species composition of fish had moderate or high similarity between transects (35 pairs with Sørensen-Chekanowski index 0.3–0.5 and 25 pairs with higher values). The species diversity and its similarity were conditioned by bottom structure and presence or absence of sea grasses and algae. The highest fish biomass was observed in the Pemzovaya Bay (29.2 g/m2, mainly large-sized Sebastes schlegelii) and at Furugelm Island (21.2 g/m2, mainly S. taczanowskii and nesting males of Hexagrammos otakii), but the biomass values < 10 g/m2 prevailed. Generally, the observed fish diversity, density, and biomass are lower in compare with the mid 1990s because of partial degradation of their habitats (disappearance of eelgrass Zostera marina) and water warming that prevents migrations of some coldwater fishes to the shallows. The most prominent decreasing is noted for Sebastes taczanowskii adults and juveniles, previously high abundant on rocky grounds, and for flounders on sandy grounds. So far as the changes of fish abundance and diversity have natural reasons, there is concluded that the effect of protection regime in the marine reserve is insignificant for fish populations.